TC2-MAC: an adaptive MAC protocol for wireless sensor network - Cun-xiang CHEN; Zun-wen HE; Jian-guang JIA; Jing-ming KUANG; Zhong-yu ZHANG; Xiao-bo XU (Tongxin xuebao)
A novel adaptive hybrid medium access control (MAC) protocol TC2-MAC has been proposed. The protocol used binary tree based time-slot-block (TSB) allocation strategy and time slot constrained carrier sense multiple access with collision avoidance (CSMA/CA) method to ensure heterogeneous sensor nodes or different types of traffic obtain personalized quality of service (QoS). In addition, it provided flexible information scheduling mechanism to improve fairness of channel access and enhance network efficiency enable. Results show that TC2-MAC has significant adaptabil-ity to the change of network traffic and network topology compared with traditional time division multiple access (TDMA) based MAC.